U.S. Special Forces - Brooks Henry (Usborne High Interest, 2014)
"An introduction to what the US Special Forces are, including the Green Berets, Navy SEALs, and Marine Force Recon, what recruits do, and jobs soldiers could learn. Includes descriptions of missions to find Osama bin Laden and to rescue an American aid worker in Somalia"--Provided by publisher.
Special forces on a mission -- Green Berets -- Navy SEALs -- Marine Force Recon -- Serving our country.
Includes bibliographical references (p. 31) and index.
3.2
K-3
Keywords: Special forces (Military science) -- United States -- Juvenile literature; Special forces (Military science); Special forces (Military science)